2010
DOI: 10.1016/j.jamcollsurg.2009.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Recipient Gender and Size Mismatch Affects Graft Success after Kidney Transplantation

Abstract: Background Female recipients of male kidneys have an inferior graft survival, and patients receiving larger kidneys relative to their body size may have a graft survival advantage. Thus, graft survival may be affected by both gender and kidney size mismatches. The objective of this study was to analyze the possible confounding effect of body mass mismatch (body mass as proxy for kidney size) between female recipients of male donor kidneys. Study Design A total of 668 kidney transplants between 1996 and 2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…DGF is the functional result of IRI in clinical renal transplantation and is defined as a requirement for dialysis within 7 days of transplantation (5). Given the sexual dimorphism of renal IRI tolerance observed in mice, we postulated that female sex would be protective against DGF and that donor-recipient size discrepancy would not account for these differences, as has been previously considered (1). To examine this hypothesis, we analyzed deceased donor renal transplants from United Network for Organ Sharing (UNOS) national registry data from 2009 to 2014, with DGF as the outcome of interest using uni-and multivariable Cox regression analysis.…”
Section: Cold Ischemia Transplantation Model To Identify Intrinsic Anmentioning
confidence: 91%
See 1 more Smart Citation
“…DGF is the functional result of IRI in clinical renal transplantation and is defined as a requirement for dialysis within 7 days of transplantation (5). Given the sexual dimorphism of renal IRI tolerance observed in mice, we postulated that female sex would be protective against DGF and that donor-recipient size discrepancy would not account for these differences, as has been previously considered (1). To examine this hypothesis, we analyzed deceased donor renal transplants from United Network for Organ Sharing (UNOS) national registry data from 2009 to 2014, with DGF as the outcome of interest using uni-and multivariable Cox regression analysis.…”
Section: Cold Ischemia Transplantation Model To Identify Intrinsic Anmentioning
confidence: 91%
“…Sex-based differences are ascribed to donor-recipient size mismatching and exposure to H-Y minor histocompatibility (1)(2)(3)(4). However, a focus on size-and immune-mediated effects has ignored the association between sex and ischemia-reperfusion injury (IRI).…”
Section: Introductionmentioning
confidence: 99%
“…Due to lack of the Y chromosome in women, antigens coded for by the Y chromosome are recognized as foreign when organ transplantation occurs from a male donor to a female recipient (McGee et al, 2010(McGee et al, , 2011. While this does not manifest immunologically as strongly as HLA incompatibility, it does have an effect of having shorter graft survival when an organ is taken from a male donor and transplanted to a female recipient (McGee et al, 2010).…”
Section: Gendermentioning
confidence: 99%
“…While this does not manifest immunologically as strongly as HLA incompatibility, it does have an effect of having shorter graft survival when an organ is taken from a male donor and transplanted to a female recipient (McGee et al, 2010). This effect is more strongly noted among bone marrow transplants, but is also present to some degree in solid organ transplants such as the kidney (Gratwohl et al, 2008).…”
Section: Gendermentioning
confidence: 99%
“…Body size is another important independent predictor for kidney volume and GFR. 11,12 Poggio et al 13 reported a strong correlation between donor body surface area (BSA) and renal function. Lee et al 14 indicated that graft kidney volume/ recipient BSA ratio was a predictor of graft function 12 months after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%